ROLE AMBIGUITY, CONFLICT AND OVERLOAD AS PREDICTORS OF EMOTIONAL EXHAUSTION: THE MEDIATION EFFECT OF TEACHING SATISFACTION AND AFFECTIVE COMMITMENT - Khalid Faris Alyamy; Loh Sau Cheong, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Owing to the emotionally demanding work context, emotional exhaustion is conceived as a general concern in special education. In a group of 216 special education teachers in the Kingdom of Saudi Arabia, this research has investigated the direct effect of role ambiguity, role conflict, and role overload on teacher’s emotional exhaustion. Participants completed the scales of emotional exhaustion, role conflict, role Ambiguity, role overload, affective engagement, and teaching satisfaction. Structural Equation Modelling Analysis (SEM) has been adopted for testing the hypotheses of this research. Results indicate that role overload had a positive significant direct impact on emotional exhaustion. Similarly, role conflict shows a positive significant direct impact on emotional exhaustion, whereas role ambiguity has a negligible direct impact on emotional exhaustion. The estimation of the indirect path between measurements of role stressors and emotional exhaustion through teaching contentment reveals that teaching contentment mediates the effect of role conflict on emotional exhaustion. The research suggests that there is no intervention effect of teaching contentment on the impact of role overload on emotional exhaustion and the impact of role overload and role conflict on emotional exhaustion is mediated by affective engagement. The research recommends further studies to explore the direct and indirect effect of role ambiguity on emotional exhaustion.